PENENTUAN WILAYAH LAUT ANTARDAERAH DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAH DAERAH - Fauzan Iqbal Harpudiansyah (Jurnal Samudra Geografi, 2023)
The territory of the Unitary State of the Republic of Indonesia is an archipelago which consists of many islands in it. The islands of Indonesia are connected to the existing oceans. The island and sea areas are divided into 34 Provinces entitled to it in accordance with Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government. This article was created to review the designation of maritime areas between regions in Indonesia based on Law Number 23 of 2014 concerning Regional Government. This article was created through a literature study with a time span from 2011 to 2020 and in Indonesian using Google Scholar, Portal Garuda, and Mendeley. This literature study found 3 articles that met the criteria.